2023
DOI: 10.3390/s24010252
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Use of Infrared Thermography in the Early Detection of Diabetic Foot Complications: A Bibliographic Review

Marina Faus Camarena,
Marta Izquierdo-Renau,
Iván Julian-Rochina
et al.

Abstract: Foot lesions are among the most frequent causes of morbidity and disability in the diabetic population. Thus, the exploration of preventive control measures is vital for detecting early signs and symptoms of this disease. Infrared thermography is one of the complementary diagnostic tools available that has proven to be effective in the control of diabetic foot. The last review on this topic was published in 2015 and so, we conducted a bibliographic review of the main databases (PubMed, the Web of Science, Coch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…IRT is capable of mapping the temperature distribution in areas of interest, providing a profile that can be obtained almost instantly, regardless of location and time [ 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IRT is capable of mapping the temperature distribution in areas of interest, providing a profile that can be obtained almost instantly, regardless of location and time [ 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the thermographic patterns of the hands and feet have been observed in patients with diabetes due to reduced blood circulation, which leads to a decrease in body temperature [ 3 , 4 , 5 , 6 , 7 , 8 ]. To visualize the metabolic state more accurately, attempts have been made to cold-challenge the test area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Henceforth, it is crucial to identify patients with foot at risk and recognize patients with early signs of diabetic foot infection, so that early intervention can be performed to prevent lower limb amputations [4][5][6][7]. Previous studies have shown that temperature fluctuations in the lower limb can be associated with diabetic foot problems [10,11]. Building on this knowledge, thermography technology such as infrared thermography (IRT) has been proposed as part of the investigative tool in the management of diabetic foot problems [10][11][12].…”
Section: Introductionmentioning
confidence: 99%